An experimental investigation of changing cut mark cross-sectional size during butchery: Implications for interpreting tool-assisted carcass processing from cut mark samples. (June 2019) - Merritt, Stephen R.
Abstract: Butchery occurs at the intersection between technology, carcass processing behavior, and animal anatomy, and records traces on fragmentary specimens including cut marks. The causal factors and contexts that generate bone surface modifications have been well-studied in experimental archaeology but the ways in which cut mark size or morphology change with time during butchery in response to tool edge dulling or carcass desiccation is currently unknown. This study examines cut mark cross-sectional width and depth change during a sequence of experimental butchery trials that control for the effects of animal size, bone portion density, tool weight, and flake versus core tool type. Mark size is measured from vinyl molds under low-power magnification (40×) and compared to more precise 3d measurement techniques. Tool type and the order of carcass segment defleshing was systematically varied across the experiment, and a linear mixed effect regression model was used to explore the impact of these fixed factors and consider random variability introduced by potential differences in the four cows butchered by eight tools. Mark width and depth samples were negatively related to the density of the portion where marks occur, tool weight had a weak, but significant influence on mark size, and marks incised at different stages in the sequence of defleshing events were similar in width and depth. With current measurement techniques and the large variability in mark size produced during butchery, it is not impossible to infer the timing of mark creation during a tool's use life or its place in a sequence of butchery events, but methodological advancement may overturn this pessimistic conclusion. Highlights: Do cut mark cross-sectional width and depth change during butchery? Butchery experiments used replicated cores and flakes to create defleshing marks Tool attributes, bone density, and order in the defleshing sequence are predictors Random effects were considered for each animal and tool, but were insignificant Bone density impacts mark size, not tool attributes or butchery sequence